ADOLESCENTS WITH HIGH-FUNCTIONING AUTISM IN ASIA: REVIEWING LEARNING BARRIERS, SOCIAL DEVELOPMENT, AND FUTURE DIRECTIONS - Zainodin, Nik Nurul Afiqah Wan; Zainal, Mohd Syazwan (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
High-functioning Autism (HFA), often used to describe individuals on the autism spectrum with average or above-average intellectual ability, presents unique challenges during adolescence—a developmental stage marked by heightened academic, social, and emotional demands. This conceptual paper examines the learning experiences of adolescents with HFA by exploring the intersection of cognitive, social, and environmental factors that shape their educational and personal trajectories. Although global literature has identified effective strategies to support this group, much of the evidence stems from Western contexts, leaving a significant gap in culturally relevant studies within Southeast Asia, particularly Malaysia. The underdiagnosis of HFA in Malaysia, coupled with insufficiently tailored educational supports, contributes to persistent barriers in school engagement, academic performance, and long-term developmental outcomes. This paper synthesizes current evidence on the challenges faced by adolescents with HFA—such as executive functioning difficulties, social communication barriers, and limited access to emotional and behavioral supports—while also highlighting intervention models including peer-mediated instruction, structured social skills training, and family-centered practices. Furthermore, it addresses systemic and cultural factors, including policy gaps and limited professional awareness, that hinder inclusive practices in Malaysian schools. Drawing on both regional insights and global perspectives, the paper proposes future directions for Malaysia, emphasizing the development of culturally adapted intervention frameworks, improved diagnostic protocols, stronger parental collaboration, and innovative service delivery methods such as tele-therapy. By underscoring the importance of localized, collaborative, and contextually sensitive approaches, this paper aims to inform educators, policymakers, and practitioners in advancing inclusive education and promoting the holistic well-being of adolescents with HFA.